2016
DOI: 10.1016/j.jneuroling.2016.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Structural prediction in aphasia: Evidence from either

Abstract: Young neurotypical adults engage in prediction during language comprehension (e.g., Altmann & Kamide, 1999; Staub & Clifton, 2006; Yoshida, Dickey & Sturt, 2013). The role of prediction in aphasic comprehension is less clear. Some evidence suggests that lexical prediction may be spared in aphasia (Dickey et al., 2014; Love & Webb, 1977; cf. Mack et al, 2013), and there is even indication that structural prediction may be spared in some people with aphasia (PWA; e.g. Hanne, Burchert, De Bleser, & Vashishth, 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
17
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 51 publications
5
17
0
Order By: Relevance
“…Some studies have found evidence suggesting that PWA do engage in prediction, particularly when provided with strong morphosyntactic cues (Hanne, Burchert, De Bleser, & Vasishth, 2015;Warren et al, 2016). Others have not found evidence of predictive processing among PWA.…”
Section: Predictive Processing In Aphasia and Healthy Agingmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have found evidence suggesting that PWA do engage in prediction, particularly when provided with strong morphosyntactic cues (Hanne, Burchert, De Bleser, & Vasishth, 2015;Warren et al, 2016). Others have not found evidence of predictive processing among PWA.…”
Section: Predictive Processing In Aphasia and Healthy Agingmentioning
confidence: 99%
“…To date, there has been relatively limited investigation of predictive processing in aphasia (Dickey, Warren, Hayes, & Milburn, 2014;Hanne, Burchert, De Bleser, & Vasishth, 2015;Mack, Ji, & Thompson, 2013;Warren, Dickey, & Lei, 2016). Study results have been mixed, with some finding evidence of intact prediction in aphasia (Dickey, Warren, Hayes, & Milburn, 2014;Hanne, Burchert, De Bleser, & Vasishth, 2015;Warren et al, 2016), and others finding evidence of impaired predictive processing (Mack et al, 2013).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…about noise or intention), which are experience-dependent. Experience-based and adaptive effects are just beginning to be explored in aphasia (DeDe, 2013a,b; Knilans & DeDe, 2015; Gahl, 2002; Schuchard & Thompson, 2014; Warren, Dickey & Lei, 2016), but understanding their role may be relevant to both improving models of aphasic language processing and advancing aphasia treatment. Only one study to date, by Gibson, Sandberg, Fedorenko, Bergen and Kiran (2015), has evaluated the rational inference account as applied to aphasic comprehension, and it provides promising support for the theory.…”
Section: Introductionmentioning
confidence: 99%
“…This supports the idea that PWA can rely on common ground and produce increasingly shorter, less complex utterances to refer to 'given' information during interaction. Finally, the presence of a communicative context has also been shown to support comprehension in aphasia: strongly predictive sentence contexts have been shown to facilitate lexical retrieval and production in PWA (Warren et al, 2016;Love & Webb, 1977;Dickey et al, 2014), though this effect is slower compared to non-brain damaged controls. Similarly, PWA showed an N400 effect like non-brain damaged controls when hearing a semantically unexpected word in a sentence, though this effect is less pronounced and delayed in aphasia (Khachatryan et al, 2017;Swaab et al, 1997;Hagoort et al, 1996).…”
mentioning
confidence: 99%